Pemanfaatan Kompos dan EM-4 pada Lahan Kritis Terhadap Serapan Hara, Pertumbuhan, dan Produksi Bawang Merah (Allium ascalonicum L) Di Kabupaten Minahasa. - Joice.M.J. Supit; Y.E.B Kamagi; L.Th. Karamoy (COCOS, 2020)
ABSTRACTField experiments on "Utilization of Compost and EM-4 in Critical Lands on NutrientUptake, Growth, and Production of Shallots (Allium ascalonicum L.) in MinahasaDistrict", with objectives in this study were Determine the optimal compost dosage foragricultural business; Determine the dose of EM-4 as an activator that can optimize theuse of compost; Utilizing critical land as productive land for agricultural activities;Improving soil physical properties, soil chemistry and soil biology for critical land becomeproductive land . The research was conducted in a field experiment by analyzing compostand soil before and after compost treatment. The compost dose treatment consisted of 0 ton/ ha as a control, 15 ton / ha; 30 ton / ha; 45 tonnes / ha and 60 tonnes / ha. The EM-4treatment consisted of 0 cc, 30cc and 60 cc / 100gr white sugar + 6 liters of water. Shallotplants as an indicator. The incubation period for compost is 2 weeks. The research methodwas a factorial experiment with a randomized block design and 3 replications. Thestatistical tests used are ANOVA and LSD analysis. The results of the study showed thatcompost treatment had a significant effect on growth and production of shallots, while EM-4 had no significant effect. Compost treatment of 45 tons / ha provides maximum nutrientuptake, growth and production of shallots.Key words: Compost, EM-4, Shallots, Critical Lands.